Alternative Policy For Efforts To Fulfill Minimum Service Standards (SPM) For Hypertension Sufferers At Seruyan Regency Health Centers In 2023 - Indah Fitri Sawaliyah; Hafizurrachman, Hafizurrachman (Sean Institute, 2024)
Introduction:The implementation of Minimum Service Standards (SPM) for hypertension sufferers in Seruyan Regency has not yet met the 100% target, only 32.2% was achieved. The aim of the research is to develop alternative policies to fulfill the SPM for hypertension sufferers. Method: This research is a qualitative research taking place in two Community Health Centers, with a total of 11 informants who are related to SPM Suffering from Hypertension. Qualitative data analysis techniques go through the stages of data reduction, data presentation and drawing conclusions.Data reduction is an activity of summarizing the main and important things. PData presentation is the presentation of reduction results for analysis of the answers from each informant as well as drawing conclusions from the interview results.Researchers made observations and reviewed documents. Qtriangulation, namely triangulation of sources, techniques and time, for validation. Results: Standards for the quantity and quality of goods/services for Hypertension sufferers carried out by Posbindu under the coordination of the Community Health Center are still not optimal, namely the lack of Tensimeters, Application and manual recording and report forms are often late. There are still Community Health Centers that do not have general practitioners, as well as Pustu, Polindes and Village Health Posts that do not have midwives and nurses, especially those in remote areas far from road access.Discussion: Alternative policies for efforts to fulfill the SPM for Hypertension sufferers at Community Health Centers can be carried out in collaboration with cross-sector Village Community Empowerment Agencies through Village funds in order to fulfill Tensimeter equipment for Posbindu activities in villages. Puskesmas and their networks should install high-speed Wi-Fi so that monitoring via WhatsApp groups of people who experience hypertension and Pustu officers can be more disciplined in submitting reports to Puksemas and the Health Service. By adding doctors, at least 2 doctors at each Puskesmas and adding midwives and nurses at Pustu, Polindes and Poskesdes, especially those in remote areas, so that we can provide maximum service to hypertension sufferers.